Scutellaria polysaccharide mediates the immunity and antioxidant capacity of giant freshwater prawn (Macrobrachium rosenbergii). (June 2023) - Sun, Lindan; Lin, Feng; Sun, Binbin; Qin, Zhendong; Chen, Keping; Zhao, Lijuan; Li, Jun; Zhang, Yulei; Lin, Li
Abstract: The giant freshwater prawn ( Macrobrachium rosenbergii ) is a commercially valuable freshwater crustacean species that frequently appears a death affected by various diseases, resulting in substantial economic losses. Improving the survival rate of M. rosenbergii is a hot and essential issue for feeding the prawns. Scutellaria polysaccharide (SPS) extracted from Scutellaria baicalensis (a Chinese medicinal herb) is conducive to the survival rate of organisms by enhancing immunity and antioxidant ability. In this study, M. rosenbergii was fed 50, 100, and 150 mg/kg of SPS. The immunity and antioxidant capacity of M. rosenbergii were tested by mRNA levels and enzyme activities of related genes. The mRNA expressions of NF-κB, Toll-R, and proPO (participating in the immune response) in the heart, muscle, and hepatopancreas were decreased after four weeks of SPS feeding (P < 0.05). This indicated that long-term feeding of SPS could regulate the immune responses of M. rosenbergii tissues . The activity levels of antioxidant biomarkers, alkaline phosphatase (AKP), and acid phosphatase (ACP) had significant increases in hemocytes (P < 0.05). Moreover, catalase (CAT) activities in the muscle and hepatopancreas, as well as superoxide dismutase (SOD) activities in all tissues, significantly decreased after four weeks of culture (P < 0.05). The results demonstrated that long-term feeding of SPS could improve the antioxidant capacity of M. rosenbergii . In summary, SPS was conducive to regulating the immune capacity and enhancing the antioxidant capacity of M. rosenbergii . These results provide a theoretical basis for supporting SPS addition to the feed of M. rosenbergii. Highlights: The immunity and antioxidant capacity of M. rosenbergii were tested. Scutellaria polysaccharide feeding did not improve the weight of M. rosenbergii. Scutellaria polysaccharide improved the antioxidant capacity of Mrosenbergii.